1997
DOI: 10.1093/emboj/16.8.1992
|View full text |Cite
|
Sign up to set email alerts
|

The activation domain of the MotA transcription factor from bacteriophage T4

Abstract: Bacteriophage T4 encodes a transcription factor, MotA, that binds to the −30 region of middle‐mode promoters and activates transcription by host RNA polymerase. We have solved the structure of the MotA activation domain to 2.2 Å by X‐ray crystallography, and have also determined its secondary structure by NMR. An area on the surface of the protein has a distinctive patch that is populated with acidic and hydrophobic residues. Mutations within this patch cause a defective T4 growth phenotype, arguing that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
(69 reference statements)
3
32
0
Order By: Relevance
“…We speculated that positioning an interaction between MotA and the C-terminal region of 70 would be reasonable, given that residues within region 4.2 of 70 normally interact with the Ϫ35 sequences of the DNA and that the MotA binding site is centered at Ϫ30 (52). The work here demonstrates that the NTD of MotA, which contains residues needed for activation (14,18), can interact with the C-terminal region of 70 . In addition, we have shown that a C-terminal peptide of MotA starting at amino acid 102 can bind DNA with a binding constant similar to that of the full-length protein.…”
Section: Vol 184 2002mentioning
confidence: 72%
See 2 more Smart Citations
“…We speculated that positioning an interaction between MotA and the C-terminal region of 70 would be reasonable, given that residues within region 4.2 of 70 normally interact with the Ϫ35 sequences of the DNA and that the MotA binding site is centered at Ϫ30 (52). The work here demonstrates that the NTD of MotA, which contains residues needed for activation (14,18), can interact with the C-terminal region of 70 . In addition, we have shown that a C-terminal peptide of MotA starting at amino acid 102 can bind DNA with a binding constant similar to that of the full-length protein.…”
Section: Vol 184 2002mentioning
confidence: 72%
“…Residues within the NTD of MotA are required for MotA activation (14,18). Induced synthesis of a cI-MotA NTD fusion, which contained MotA amino acids 1 to 97, in cells containing the ␣-70 chimera resulted in a significant increase in ␤-galactosidase activity (Fig.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The rpd1-2 and rpd1-1 mutations occur in the first and second domains, respectively, suggesting that these domains are important for the function of RPD1. It is notable that these domains might be structurally related to the winged helix proteins, which are involved in various regulatory functions through DNA binding, RNA binding, or protein-protein interaction (Clark et al, 1993;Ramakrishnan et al, 1993;Fogh et al, 1994;Finnin et al, 1997;Groft et al, 1998;Schwartz et al, 1999;Zheng et al, 1999;Gajiwala and Burley, 2000;Okuda et al, 2000;Kamada et al, 2001;Schwartz et al, 2001;Wilce et al, 2001;Selmer and Su, 2002;Zheng et al, 2002;Alfano et al, 2004;Dong et al, 2004;Wei et al, 2004). Studies focusing on this unique structure should provide insight into the molecular function shared by the RPD1 family proteins.…”
Section: Rpd1 Belongs To a Novel Protein Family Specific To The Plantmentioning
confidence: 99%
“…MotA was first identified through the isolation of T4 motA 2 phages, which were shown to be defective in the expression of a set of T4 middle gene products (Mattson et al, 1974(Mattson et al, , 1978. Structural and biochemical studies have indicated that MotA contains two distinct domains: an N-terminal domain (NTD) that is formed by five a-helices and a short b-ribbon (Li et al, 2002) and houses a transcription activation function (Finnin et al, 1997;Gerber & Hinton, 1996;Pande et al, 2002) and a C-terminal domain (CTD) that by itself is capable of binding DNA (Pande et al, 2002) and is composed of a novel 'double wing' motif of three a-helices interspersed with six b-strands (Li et al, 2001). …”
mentioning
confidence: 99%